2009
DOI: 10.1056/nejmoa0906768
|View full text |Cite
|
Sign up to set email alerts
|

Abacavir–Lamivudine versus Tenofovir–Emtricitabine for Initial HIV-1 Therapy

Abstract: BACKGROUND-The use of fixed-dose combination nucleoside reverse-transcriptase inhibitors (NRTIs) with a nonnucleoside reverse-transcriptase inhibitor or a ritonavir-boosted protease inhibitor is recommended as initial therapy in patients with human immunodeficiency virus type 1 (HIV-1) infection, but which NRTI combination has greater efficacy and safety is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
228
3
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 284 publications
(252 citation statements)
references
References 12 publications
(10 reference statements)
13
228
3
8
Order By: Relevance
“…Currently, treatment for such diseases focuses on drugs and vaccines that specifically target the viral proteins or inhibit host-viral interactions 2,3 . However, the nature of lentiviral infections, whereby the virus, such as human immunodeficiency virus (HIV), invades immune cells and integrates into the host genome to establish its latent infection, has created a huge obstacle with respect to developing efficient vaccines 4,5 .…”
mentioning
confidence: 99%
“…Currently, treatment for such diseases focuses on drugs and vaccines that specifically target the viral proteins or inhibit host-viral interactions 2,3 . However, the nature of lentiviral infections, whereby the virus, such as human immunodeficiency virus (HIV), invades immune cells and integrates into the host genome to establish its latent infection, has created a huge obstacle with respect to developing efficient vaccines 4,5 .…”
mentioning
confidence: 99%
“…18,19 In accordance with other studies comparing abacavir/ lamivudine and tenofovir/emtricitabine, patients taking abacavir/lamivudine showed higher plasma lipids at baseline as compared to patients taking tenofovir/emtricitabine. 13,14,[20][21][22] Although differences were not significant at 48 weeks, it may be of interest that through the study decreases in triglycerides, decreases in total-to-HDL cholesterol, and increases in HDL cholesterol tended to be higher when raltegravir (instead of ritonavir-boosted PIs) was combined with abacavir/lamivudine than with tenofovir/emtricitabine. This was also consistent with a significantly lower proportion of patients showing HDL cholesterol < 40 mg/dl at 48 weeks when treated with abacavir/lamivudine compared to tenofovir/emtricitabine, and a nonsignificant higher decrease in the total-to-HDL cholesterol ratio at 48 weeks in patients treated with abacavir/ lamivudine plus raltegravir relative to patients treated with tenofovir/emtricitabine plus raltegravir.…”
Section: Discussionmentioning
confidence: 85%
“…32 A subgroup analysis of ACTG study A5202 noted the TDF-3TC NRTI combination to have fewer virologic failures than abacavir (ABC)-3TC in patients with HIV-1 RNA viral load $ 100,000 copies/mL when combined with EFV or the boosted PI ATZ (7% failure rate at 48 weeks compared with 14%; hazard ratio [HR], 2.33; 95% confidence interval [CI]: 1.46 to 3.72; P , 0.001). 29 When comparing groups in a higher virologic strata (HIV-1 viral load $ 100,000 copies/mL), patients taking ABC-3TC combined with boosted-ATZ had higher rates of virologic failure than those taking ABC-3TC combined with EFV (HR, 1.68; 95% CI: 1.08 to 2.60; P = 0.019). 37 The Altair study found that a quadruple NRTI regimen (TDF-FTC-ZDV-ABC) was inferior to TDF-FTC-EFV, mostly due to therapy discontinuations from adverse events in the ITT analysis, although there was no difference of the latter to TDF-FTC-ATZ-r. 30 The STARTMRK study was the first study comparing TDF-FTC-EFV to an integrase inhibitor-based regimen.…”
Section: Efficacymentioning
confidence: 98%
“…The fixed-dose combination Atripla and the individual components have been evaluated in a number of clinical trials in comparison to alternate agents including NNRTI (nevirapine, etravirine [ETR], rilpivirine [RPV]), ritonovir-boosted protease inhibitor (PI-r) (lopinavir-ritonavir [LPV-r], atazanavir-ritonavir [ATZ-r]) integrase inhibitors (raltegravir [RAL], elvitegravir), and CCR-5 inhibitors (maraviroc). [25][26][27][28][29][30][31][32][33][34][35] In the studies to date, largely of noninferiority design, and using the primary endpoints as defined by the studies, Atripla has not been beaten for efficacy by any other agent.…”
Section: Efficacymentioning
confidence: 99%